How This Pandamic Situation Become An Opportunity For Self-Help Group - TIWARI, MEGHA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Engaging ladies has for some time been seen as the answer for some worldwide issues. Social orders that focus on ladies' strengthening show better advancement records and are better administered, steadier, and less inclined to brutality. Interestingly, social orders that compel ladies' instructive and work openings, and that deny ladies an equivalent political voice, are more unfortunate and more inclined to defilement. Ladies enduring the worst part of the drawn-out financial and cultural outcomes of the COVID-19 emergency, even the restricted additions, and hard-won advancement ladies have made in the previous twenty years are in danger of being moved back. Coronavirus has amplified the inescapable injustice that keeps on restricting ladies chances, going about as an incredible speaker of disparity. SHGs have arisen as cutting edge laborers and the last mile interface among governments and individuals during this emergency by reacting to COVID-19; they are making veils, hand sanitizers, PPE units, circulating bring home apportion, dispersing COVID-19 related data, and running local area kitchens to take care of the defenseless is reflected in this paper.